Effect of Graded Levels of Shatavari Root Meal on the Body Weight, Feed Conversion Ratio, Biochemical Attributes and Immune Competence Traits of Coloured Chicken - Yadav, Binay Kumar; Shukla, Pankaj Kumar; Bhattacharyya, Amitav; Roy, Debashis; Sharma , Aditya; Sirohi, Rajneesh (International Journal of Livestock Research, 2018)
Two hundred and ten straight run, day old coloured chicken (Chabro) were randomly distributed into seven dietary treatments T1- basal diet (broiler starter diet till 4 weeks, broiler finisher diet till eight weeks), T2- T1+0.25% Shatavari root meal (SRM), T3- T1+0.5% SRM, T4- T1+0.75% SRM, T5- T1+1% SRM, T6- T1+1.25% SRM and T7- T1+1.5% SRM, having three replicates each with ten coloured chicken. T2 birds had a significantly better (P<0.05) FCR at 2nd week as compared to T1, T6 and T7. T3 coloured birds had significantly better (P<0.01) cell mediated immune response than T1, T4, T5 and T7 at 8 weeks of age. T1 and T2 had significantly higher (P<0.01) plasma cholesterol than the other treatment groups. Hence, dietary supplementation of Shatavari meal @ 0.5% and above reduced plasma cholesterol in coloured chicken. Further, dietary supplementation of Shatavari root meal @ 0.5% may improve growth performance and immunity in coloured chicken.